Cyclicality of schooling: New evidence from unobserved components models - Barbara Sadaba; Sunécica Vujiéc; Sofia Maier (Bank of Canada, 2020)
In this paper, we present new evidence from unobserved components time-series models on the cyclical behavior of the demand for education relative to economic cycles. We investigate the cyclical properties of schooling decisions, the time-varying exposure of these decisions to changes in the state of the macro economy, and the relative importance of shocks that drive economic fluctuations on the demand for schooling. To this end, we perform a trend-cycle decomposition of enrollment ratios for the United Kingdom over the period 1995Q1 to 2019Q4. We first establish the presence of a persistent cyclical process in the demand for schooling independent of a slow-moving trend. We then show that the direction of the effect of the economic cycle on schooling decisions (i.e., pro-cyclical, counter-cyclical, a-cyclical) is largely time-dependent, together with the degree of synchronization. Importantly, we find that changes in the demand for schooling are largely explained by economic cycles. We note, however, that the effects are different for different subsamples based on demographic characteristics..
Keywords: E3; I2; J2; C32; 330; Business fluctuations and cycles; Econometric and statistical methods